Up‐regulation of Rac1 in the bronchial smooth muscle of murine experimental asthma. Issue 1 (21st February 2019) - Kai, Yuki; Motegi, Momoko; Suzuki, Yuta; Takeuchi, Hiroto; Harada, Yui; Sato, Fumiaki; Chiba, Yoshihiko; Kamei, Junzo; Sakai, Hiroyasu
Abstract: There has been considerable research on the involvement of RhoA/Rho kinase signalling in smooth muscle contractions. However, only a few reports have addressed the specific role of Rac1, which is a member of the Rho GTPase superfamily. Therefore, this study investigated the role of Rac1‐related pathways in bronchial smooth muscle (BSM) contractions. Bronchial rings isolated from mice were suspended in an organ bath, and the isometric contractions of circular smooth muscles were monitored. The phosphorylation of myosin light chains (MLCs) was analysed by immunoblotting. The Rac1 inhibitor EHT1864 inhibited carbachol (CCh)‐induced BSM contractions, although high K + depolarization‐induced BSM contractions were not significantly attenuated by EHT1864. Moreover, high K + ‐ and phorbol 12, 13‐dibutyrate (PDBu; PKC activator)‐induced contractions were not attenuated by Rac1 inhibition, whereas sodium fluoride (NaF)‐induced force development was inhibited by EHT1864. The gene and protein expression of Rac1 was increased in the BSM of a murine model with antigen‐induced airway hyper‐responsiveness (AHR). In addition, an increased force of the BSM contractions in AHR was suppressed by EHT1864 treatment, suggesting that the up‐regulation of Rac1 is involved in AHR. These findings suggest that an increase in Rac1‐mediated signalling is involved in the augmented contractions of BSMs in antigen‐induced AHR mice.